Respostas
respondido por:
8
z^4 = (z²)²
z² = (√3 + i)² = 3 + 2.√3.i - 1
z² = 2 + 2√3i
(z²)² = (2+2√3i)² = 4 + 8√3i - 4.3
z^4 = -8 + 8√3i
z² = (√3 + i)² = 3 + 2.√3.i - 1
z² = 2 + 2√3i
(z²)² = (2+2√3i)² = 4 + 8√3i - 4.3
z^4 = -8 + 8√3i
respondido por:
9
Boa tarde Valdirene
z = √3 + i
z = 2*(√3/2 + i/2)
z = 2*(cos(30) + sen(30)*i)
z⁴ = 2⁴ * (cos(4*30) + sen(4*30)i)
z⁴ = 16 * (-1/2 + √3/2)
z⁴ = -8 + 8√3i
z = √3 + i
z = 2*(√3/2 + i/2)
z = 2*(cos(30) + sen(30)*i)
z⁴ = 2⁴ * (cos(4*30) + sen(4*30)i)
z⁴ = 16 * (-1/2 + √3/2)
z⁴ = -8 + 8√3i
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás